Assessment of Post-Procedural Mitral Regurgitation and Its Mechanisms Using 3D Transthoracic Echocardiography Following PMBC in Patients with Rheumatic Mitral Stenosis - Zakria, Hira; Khan, Muhammad Nadir; Azhar, Amina; Zahoor, Sidra; Amjad, Faizan; Khan, Fasih Ullah (Indus Journal of Bioscience Research, 2025)
Background: Rheumatic mitral stenosis (MS) remains a significant cardiovascular burden in low- and middle-income countries (LMICs). Percutaneous mitral balloon commissurotomy (PMBC) is the standard intervention, but mitral regurgitation (MR) remains a major complication. Objectives: This study aimed to determine the incidence, severity, and underlying mechanisms of MR following PMBC using three-dimensional transthoracic echocardiography (3D TTE). Methods: In this prospective study, 300 patients with severe symptomatic rheumatic MS underwent PMBC from September, 2023 to December, 2024. Baseline and post-procedural echocardiographic assessments were performed, and mechanisms of MR were classified using 3D TTE. Results: New or worsening MR occurred in 41% of patients post-PMBC. MR was mild in 16%, moderate in 15%, and severe in 10% of cases. Commissural MR was the most common mechanism of significant MR (32%), followed by commissural MR with posterior leaflet involvement (26%) and central MR (17%). Leaflet tear involving the central scallops accounted for 10 of the 32 severe MR cases. Conclusions: MR is a frequent complication following PMBC, with distinct mechanistic patterns identifiable via 3D TTE. Understanding these mechanisms may inform clinical decision-making and long-term clinical outcomes.